Real-time sea-level gauge observations and operational oceanography - Mourre, Baptiste; Crosnier, Laurence; Le Provost, Christian (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2006)
Theme issue ‘Sea level science’.-- 18 pages, 11 figures The contribution of tide-gauge data, which provide a unique monitoring of sea-level variability along the coasts of the world ocean, to operational oceanography is discussed in this paper. Two distinct applications that both demonstrate tide-gauge data utility when delivered in real-time are illustrated. The first case details basin-scale operational model validation of the French Mercator operational system applied to the North Atlantic. The accuracy of model outputs in the South Atlantic Bight both at coastal and offshore locations is evaluated using tide-gauge observations. These data enable one to assess the model's nowcasts and forecasts reliability which is needed in order for the model boundary conditions to be delivered to other coastal prediction systems. Such real-time validation is possible as long as data are delivered within a delay of a week. In the second application, tide-gauge data are assimilated in a storm surge model of the North Sea and used to control model trajectories in real-time. Using an advanced assimilation scheme that takes into account the swift evolution of model error statistics, these observations are shown to be very efficient to control model error, provided that they can be assimilated very frequently (i.e. available within a few hours) Part of this work was funded by the Marine Environment and Security for the European Area project (MERSEA) supported by the European Commission under the 6th framework programme. The other part was supported by Centre National Etudes Spatiales (CNES) and Centre National de la Recherche Scientifique (CNRS). The Florida Current cable data are made freely available on the Atlantic Oceanographic and Meteorological Laboratory web page (www.aoml.noaa.gov/phod/floridacurrent) and are funded by the NOAA Office of Climate Observations Peer reviewed